Expansion of the distribution of Sephanoides sephaniodes (Trochilidae: Aves) in Argentina - Marinero, Nancy Verónica (2012)
The present work report the expansion of the distribution of Sephanoides sephaniodes toward the west-central of Argentina. It discusses possible causes of dispersion and ecological consequences of them.